Empirical evidence on payment media costs and switch points - ten Raa, Thijs; Shestalova, Victoria (Journal of Banking & Finance, 2004)
This paper recovers micro cost schedules of consumers’ payment instruments from aggregate transaction costs. We assume that only two moments of the size distribution of payments matter: the number and volume of transactions. These variables explain the transaction costs of currency and debit card payments with much precision for a representative 1998 sample of Dutch retailers. The results imply that low fixed transaction costs favor currency for small transactions, while low variable transaction costs favor debit card payments for large transactions. The switch point is 30 Euros, but including the hidden costs of currency would lower it to 13 Euros.